Free School Meals Policy as a Learning Framework for MBG in Indonesia: A Systematic Literature Review - Nurya Hartika Sari; Andries Lionardo; M. Husni Thamrin; Raniasa Putra (Green Publisher Indonesia, 2025)
This article aims to systematically map existing literature on the implementation of free school meals policy using a Systematic Literature Review (SLR) approach. A total of 140 articles were initially identified and screened through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, resulting in 33 articles selected for in-depth analysis. The selected publications were further examined using VOSviewer to identify thematic patterns and keyword relationships. The analysis reveals three main clusters of research focus: (1) the impact of free school meals on health and nutrition policy; (2) technical implementation and governance of school meal provision; and (3) organizational dimensions, management structures, and the role of beneficiaries. The findings indicate that the success of free school meal programs depends on multiple factors, including policy stability, multi-level collaboration among actors, effective food management mechanisms, and regular program evaluation. This study recommends that Indonesia's Makan Bergizi Gratis (MBG) program integrate these dimensions holistically—ensuring quality assurance, food safety, and an inclusive social dining experience for all students as beneficiaries.